Sustainable Energy: A Case Study of an Alpaca Wool Production Unit in Cashapata San Mateo-Huarochiri-Peru - Gutiérrez, Beatriz Luisa Salvador (2024)
In Peru, with the world's largest alpaca population and as the world's leading producer of alpaca fiber, many rural families in high Andean areas depend on alpaca raising and the sale of their fiber as their main source of income. The Cashapata production unit in the rural community of San Antonio, San Mateo district, Huarochiri province, Lima department, is made up of 45 families that sell the fiber at very low prices to the collector. Lack of access to electricity has hindered the transformation of fiber into yarn. This case study focused on the adoption of solar technology to address this transformation challenge. The solar resource and community readiness were assessed. The results showed an on-site solar radiation of 5.26 Kwh/m2.day, with each transformation process such as shearing, terma, dryer, carder and solar spinner being successful. In addition, by recognizing and valuing the traditional knowledge accumulated over generations, it facilitated the adoption of solar technologies for fiber processing. This participatory approach promoted collaborative learning and community empowerment, highlighting the potential of solar energy to drive sustainable development in alpaca wool production.